Qualitative methods in workplace learning - Fabritius, Hannele (Qualitative and Quantitative Methods in Libraries, 2017)
Methods of learning in the workplace will be introduced. The methods are connect to competence development and to the process of conducting development discussions in a dialogical way. The tools developed and applied are a fourfold table, a cycle of work identity, a plan of personal development targets, a learning meeting and a learning map. The methods introduced will aim to better learning at work.